PANDANGAN SUFISTIK KETUHANAN DALAM PUISI AL HALLÄ€J DAN ABDUL HADI W.M DALAM ANALISIS SASTRA BANDING - nur kholis (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2021)
This article aims to look at the Sufistic view of divinity from two different poems, namely Arabic poetry and Indonesian poetry. The side that is compared between the two poems is the view of the unity of God and his servant. This article uses a literary appeal approach, which compares two literary works from two different countries, also different languages â€‹â€‹and different cultures. The research results of this article found that there are similarities and similarities between two literary works in the form of poetry from two countries, namely Arabic and Indonesia. The poetry that is compared from Arabic is from the anthology of Sufistic poetry by al HallÄj which describes the feeling of his closeness to his god, and poetry from Indonesia by Abdul Hadi which also expresses the closeness of the soul of a servant and his god with his poetry